Framework for Cassation Appeal of Decisions on the Imposition of Administrative Sanctions - Evgenyi Fahratdinovich Rashidov; Yuryi Pavlovich Chulkov (Сибирское юридическое обозрение, 2011)
This article analyses the changes made in the Code of Arbitrational Procedure of the Russian Federation intended to restrict the right of appeal of decisions on the imposition of administrative sanctions.